Building Rhetorical Theory through Discursively Constructed Borders. Issue 1 (2nd January 2016) - Monty, Randall W.; Cavazos, Alyssa G.
ABSTRACT: The contacted disciplines of Border Studies, Rhetoric and Composition/Writing Studies, and Critical Discourse Analysis are each interested in how borders function and are constructed. However, since each discipline approaches the topic from individualized situations, the scholarship remains under-synthesized. As a result, few usable methodologies and theories for working across contexts, both in terms of physical space and disciplinary place, have been developed. By working within the contact zone of these disciplines, we aim to build a theoretical framework for analyzing the construction of borders through the ways local stakeholders compose and interpret discourses. With this approach, we find that the ways these stakeholders rhetorically construct their own border regions can align with scholarly representations, but at the same time, these constructions often contradict the prominent depictions encountered through popular culture, news media, and public policy.